PENGARUH MARKETING MIX TERHADAP KEPUASAN KONSUMEN (STUDI KASUS WAROENG MIE MAK TUR BONDOWOSO) - Maharani, Puteri Devi; Setianingsih, Wahyu Eko; Rahayu, Jekti (Fakultas Ekonomi dan Bisnis, 2022)
In the business world, customers are an important factor to develop and maintain a business. When customers get satisfaction, it can lead to a high sense of loyalty and always make repeat purchases so that they do not affect other parties. The tight competition is marked by the increasing number of noodle stalls in Bondondowoso, one of the businesses that is also experiencing intense competition today is Waroeng Mie Mak Tur. The rise and fall of the number of consumers when making purchases is a problem at Waroeng Mie Mak Tur Bondowoso, causing consumer satisfaction which is expected to increase sales. This study aims to determine the effect of product, price, place, promotion, people/employees, physical evidence and process on consumer satisfaction. This type of research is quantitative with 80 samples used with purposive sampling technique. The analysis used is multiple linear regression analysis. From the results of the analysis, it can be seen that product, place, promotion, people/employees, physical evidence and processes have a significant effect on consumer satisfaction, while price has no significant effect on consumer satisfaction.